# Trigonometry

posted by .

Simplify the expression using trig identities:
1. (sin4x - cos4x)/(sin2x -cos2x)

2. (sinx(cotx)+cosx)/(2cotx)

• Trigonometry -

1.
I am sure you mean
(sin^4 x - cos^4 x)/(sin^2 x - cos^2 x)
= (sin^2 x + cos^2 x )((sin^2 x - cos^2 x)/(sin^2 x - cos^2 x)
= (sin^2 x + cos^2 x)
=1

2.
(sinx(cotx)+cosx)/(2cotx)
= (sinx(cosx/sinx) + cosx)/(2cosx/sinx)
= (cosx + cosx)(sinx/(2cosx)
= 2cosx(sinx)/(2cosx)
= sinx

## Similar Questions

1. ### Trigonometry.

( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! Generally these are done by changing everything to sines and cosines, unless you see some obvious identities. Also generally, it is best to start with the more complicated side …
2. ### Math - Trig - Double Angles

Prove: sin2x / 1 - cos2x = cotx My Attempt: LS: = 2sinxcosx / - 1 - (1 - 2sin^2x) = 2sinxcosx / - 1 + 2sin^2x = cosx / sinx - 1 = cosx / sinx - 1/1 = cosx / sinx - sinx / sinx -- Prove: 2sin(x+y)sin(x-y) = cos2y - cos2x My Attempt: …
3. ### math

sin2x-cotx = -cotxcos2x Using the various trigonometric identities(i.e. double angle formulas, power reducing formulas, half angle formulas, quotient identities, etc.) verify the identity. I first added cotx to both sides to get sin2x …
4. ### Trig

Simplify: (cosx + cos2x + cos3x + cos4x + cos5x + cos6x) / (sinx + sin2x + sin3x + sin4x + sin5x + sin6x) into a single Cotangent function. Using the sum-to-products, I was able to get remove some of the addition in attempts to get …
5. ### Math

simplify (cos4x-cos2x)/(sin4x+sin2x) the answer choices are : cotx, tanx, cotxtanx, or 1
6. ### Trig

Prove the following functions: (sinx+sin2x)/(1+cosx+cos2x)=tan x (cos3x/sinx)+(sin3x/cosx)=2cot2x tan2x=(2/cotx-tanx) theses are due in the am. Fastness would be great?
7. ### Trigonometry

Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/sinx+cosx = cscxtanx/sinx+cosx Is the correct answer cscxtanx/sinx+cosx?
8. ### trigonometry

can i use factoring to simplify this trig identity?